Wireless Sensor Network for in situ Soil Moisture Monitoring - Fang, Jianing; Hu, Chuheng; Smaoui, Nour; Carlson, Doug; Gupchup, Jayant; Musaloiu-E., Razvan; Liang, Chieh-Jan Mike; Chang, Marcus; Gnawali, Omprakash; Budavari, Tamas; Terzis, Andreas; Szlavecz, Katalin; et al. (SENSORNETS, 2021)
We discuss the history and lessons learned from a series of deployments of environmental sensors measuring soil parameters and CO2 fluxes over the last fifteen years, in an outdoor environment. We present the hardware and software architecture of our current Gen-3 system, and then discuss how we are simplifying the user facing part of the software, to make it easier and friendlier for the environmental scientist to be in full control of the system. Finally, we describe the current effort to build a large-scale Gen-4 sensing platform consisting of hundreds of nodes to track the environmental parameters for urban green spaces in Baltimore, Maryland.